2020
DOI: 10.3926/jairm.160
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of wildlife strikes to aircraft in Brazil: 2011-2018

Abstract: Purpose: Aircraft accidents due to wildlife hazards have become a growing safety and economic problem to the Brazilian and international aviation industries. These safety occurrences have resulted in significant direct and indirect economic losses as well injuries and fatalities worldwide. The purpose of this study was to develop empirical information obtained from the analysis of wildlife strike and aircraft operations data in Brazil that could be used for accident prevention efforts.Design/methodology: The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Additionally, allowing teacher autonomy supported a seamless transition to online platforms during the COVID-19 pandemic, which may translate well to a weather event without having to cancel class. Those who are researchers within the scholarship of teaching and learning community find this to be no surprise (Kahu, 2011;Ayuka & Jacobs, 2018;Keller et al, 2020). This research project examines the experience of one assistant professor of aeronautical science who implemented Nearpod into her classroom prior to COVID-19 mandates and how that was received by students before, during, and after the experience.…”
Section: Tracy Parodi Embry Riddle Aeronautical Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, allowing teacher autonomy supported a seamless transition to online platforms during the COVID-19 pandemic, which may translate well to a weather event without having to cancel class. Those who are researchers within the scholarship of teaching and learning community find this to be no surprise (Kahu, 2011;Ayuka & Jacobs, 2018;Keller et al, 2020). This research project examines the experience of one assistant professor of aeronautical science who implemented Nearpod into her classroom prior to COVID-19 mandates and how that was received by students before, during, and after the experience.…”
Section: Tracy Parodi Embry Riddle Aeronautical Universitymentioning
confidence: 99%
“…Information obtained from the scientific analyses of wildlife strikes to aircraft has indicated that different safety strategies to mitigate such risks are vital (Misra et al, 2022;Tella & Mendonca, 2023). According to Mendonca et al (2020), these strategies should include research and innovative use of current technologies. The purpose of this study was to explore the use of UAS technologies at night by developing and refining a concept of operations to support data collection and analysis during a nighttime WHA.…”
Section: Background and Problem Statementmentioning
confidence: 99%
“…Information obtained from the scientific analyses of wildlife strikes to aircraft has indicated that different safety strategies to mitigate such risks are vital (Misra et al, 2022;Tella & Mendonca, 2023). According to Mendonca et al (2020), these strategies should include research and innovative use of current technologies. The purpose of this study was to explore the use of UAS technologies at night by developing and refining a concept of operations to support data collection and analysis during a nighttime WHA.…”
Section: Background and Problem Statementmentioning
confidence: 99%